Analytical Approach on the Law Regarding Sexual Violence between Indonesia and the United Kingdom - Irvanaries Irvanaries; David Tan (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
Criminal deeds bring disaster to the life of the people in general, and rights of many are to be stripped of from them without their consent which is then becomes the urgency on why criminal law needs to be enacted and applied. In its provisions, criminal law regulates about sexual violences. It has a potential to caused harm both physically and mentally towards its victim. However, the problem with the system is that at some point, the ideal justice is not met in its enforcement. Indonesian constitution is yet to enact a regulation to restrain or to impose more assertive measures on sexual violences. One of the examples is how rape is recognized only if the victim is a woman who is not the wife of the perpetrator. This idea does not fully protect the right of others who becomes a victim of sexual assault which doesn’t fulfil the ideal justice within the constitution. Comparing to how the United Kingdom sentenced Reinhard Sinaga to prison for life as the consequences of his deed, the authors want to create a comparison on the criminal law in both countries based on Rome Statute of ICC and to discover in what way can Indonesia’s criminal law improve.